Surrogate endpoints: from definition to meta-analytic framework 1 - Molenberghs, Geert (Henry Stewart Talks, 2019)
Discrete surrogates, Prentice’s definition, Subsequent developments, Single-trial validation framework, Meta-analytic frameworks